2009
DOI: 10.1248/bpb.32.121
|View full text |Cite
|
Sign up to set email alerts
|

Validation of HPLC-UV Methods for Quantitatively Determining Landiolol and Its Major Metabolite in Human Blood

Abstract: Landiolol hydrochloride is a newly developed cardioselective, ultra short-acting b 1 -adrenergic receptor blocking agent. Landiolol hydrochloride has much higher cardioselectivity (b 1 /b 2 ϭ255) than currently available b 1 -blockers, such as esmolol hydrochloride (b 1 /b 2 ϭ33).1) This drug is rapidly hydrolyzed by both carboxylesterase in the liver and pseudocholinesterase in the plasma 2) to an inactive metabolite (M-1) with a rapid elimination half-life of about 4 min, which is significantly shorter than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The sample preparation method developed in this study was very simple compared with the previously reported approach [13]. The fluorescence intensity of landiolol was weak and was not much different from that of UV absorption when the authentic compound was analyzed using the previously reported method.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The sample preparation method developed in this study was very simple compared with the previously reported approach [13]. The fluorescence intensity of landiolol was weak and was not much different from that of UV absorption when the authentic compound was analyzed using the previously reported method.…”
Section: Discussionmentioning
confidence: 89%
“…However, the employment of fluorescence detection in our present method dramatically reduced the chromatographic background signals when the blood sample was analyzed, resulting in the achievement of a sample preparation with 5 times higher sensitivity using a simple purification procedure. For UV detection in the previous method, further complicated purification steps for sample preparation were required [13]; a process which most likely would yield quantitative errata because of the rapid continuous degradation of landiolol after blood sampling (even in cases where blood samples were immediately mixed with ice-cold ethanol after sampling, 10-30% of landiolol were degraded). Thus, the use of enzyme inhibitors, such as neostigmine in the present study, is essential to prevent landiolol degradation, especially when blood is collected in the operation theater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several methods for the determination of landiolol in human blood have been reported [12,13]. However, based on high performance liquid chromatography (HPLC) with UV or fluorescence detection, these methods have inadequate sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…In previous assays [12,13], blood samples were immediately mixed with an ethanolic solution of neostigmine to stabilize landiolol prior to sample preparation.…”
Section: Introductionmentioning
confidence: 99%